B, N Dual Doped Coral-Like Carbon Framework With Superior Pseudocapacitance and Surface Wettability - Han, Lu; Chen, Xu; Zeng, Shijie; Liu, Jia; Yang, Zhongli; Wang, Zhiqiang; Li, Liang; Wang, Haibao; Hou, Zhanbin; Xu, Min (Frontiers in Materials, 2021)
Carbon-based materials are usually considered as conventional electrode materials for supercapacitors (SCs), therefore it is meaningful to enhance supercapacitive capacity and cycling stability via rational surface structure design of carbon-based materials. The bio-inspired coral-like porous carbon structure has attracted much attention recently in that it can offer large surface area for ion accommodation and favor ions-diffusion, promoting its energy storage capacity. Herein, we designed a superiorly hydrophilic B, N dual doped coral-like carbon framework (BN-CCF) and studied its surface wettability via low-field nuclear magnetic resonance relaxation technique. The unique coral-like micro-nano structure and B, N dual doping in carbon framework can enhance its pseudocapacitance and improve surface wettability. Therefore, when used as electrodes of SCs, the BN-CCF displays 457.5 F g−1 at 0.5 A g−1, even when current density increases 20 folds, it still exhibits high capacitance retention of 66.1% and superior cycling stability. The symmetrical SCs assembled by BN-CCF electrodes show a high energy density of 14.92 Wh kg−1 (600 W kg−1). In this work, simple structural regulation with B, N dual doping and surface wettability should be considered as effective strategy to enhance energy storage capacity of carbon-based SCs.